Night-time oxidation at the air–water interface: co-surfactant effects in binary mixtures. Issue 6 (21st September 2022) - Sebastiani, Federica; Campbell, Richard A.; Pfrang, Christian
Abstract : The ageing of organic-coated aqueous aerosols at night is investigated by reacting NO3 with binary surfactant mixtures floating on water. Abstract : The ageing of organic-coated aqueous aerosols at night is investigated by reacting NO3 with binary surfactant mixtures floating on water. The surfactants are oleic acid (OA), methyl oleate (MO) and stearic acid (SA). Deuterated surfactants mixed with hydrogenous surfactants were studied using neutron reflectometry to determine the reaction kinetics of organic two-component monolayers with NO3 at the air–water interface for the first time. We measured the rate coefficients for OA monolayers, mixed with hydrogenous co-surfactant MO or SA to be (3 ± 1) × 10 −8 cm 2 per molecule per s or (3.6 ± 0.9) × 10 −8 cm 2 per molecule per s and MO monolayers mixed with hydrogenous co-surfactant OA or SA to be (0.7 ± 0.4) × 10 −8 cm 2 per molecule per s or (3 ± 1) × 10 −8 cm 2 per molecule per s. The initial desorption lifetimes of NO3, τ d, NO3, 1, were 8 ± 3 ns, 14 ± 4 ns, 12 ± 3 ns and 21 ± 10 ns. The approximately doubled desorption lifetime for MO–SA compared to the other mixtures is consistent with a more accessible double bond associated with the larger area per molecule of MO in the presence of SA facilitating NO3 attack. The significantly slower reactive loss of MO–OA compared to a MO monolayer demonstrates that multi-component surfactant mixtures need to be studied in addition to single-component monolayers. Such a retarded decay would cause the residence time to change from ca. 4 to 22 minutes associated with increased transport distances of surfactant species together with any other pollutants that may be protected underneath the surfactant film.